Sistematik Literature Review: Penyelesaian Audit, Penelaahan Subsequent Event, Laporan Auditor Dan Management Latter, Penemuan Fakta - Andriyanto Andriyanto; Januar Arafi; Maulia Nur Oktavia; Satria Dwiky Sektiawan; Herlina Manurung (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This article aims to present an in-depth Systematic Literature Review related to several key aspects in the audit domain, including Audit Completion, Subsequent Event Review, Auditor's Report, Management Letter, and Fact Finding. By adopting a systematic approach, this research summarizes and analyzes related scientific literature to provide a comprehensive view of the latest developments in each of these aspects. The results of this literature review provide in-depth insight into strategies and methodologies in completing audits, evaluating the impact of subsequent events, the role and process of preparing auditor reports and management letters, as well as finding relevant facts in the audit process. This research not only provides an overview of current practices in the world of auditing, but also identifies knowledge gaps that may provide a basis for future research. By understanding in depth the key aspects of the auditing process, this article makes an important contribution to the development of audit science and facilitates a better understanding of future challenges and opportunities.